Clinical Correlation Between Alopecia Areata and Salmon Patches: A Case Series - Musbah , Fauzia (AlQalam Journal of Medical and Applied Sciences, 2024)
Alopecia areata (AA) has different clinical types moreover its severity can be predicted by the extra-follicular involvement such as nails, eyes, and salmon patch (SP) on the nape of the neck. As provided by previous authors the aim of this study was to determine whether the presence of a salmon patch on the midline of the nape of the neck and whether its size is related to the recurrence of AA after treatment withdrawal and a more severe prognosis. We report a case series of 24 patients with recurrent AA having congenital SP from March 2022 to April 2023 at Tripoli Central Hospital (TCH) and in a private clinic. We found that the majority of the cases were diagnosed with recurrent AA ophiasis (AAO) (n= 11, 45.8%) of which Ten (91%) of them were females and that can be interpreted as an indication of severity since AAO carries the risk of the worst prognosis. The other cases were AA Universalis (n=9, 37.5%), AA Totalis (n=2, 8.3%), and multiple patches AA (n=1, 4.2%). and 11 (45.8%) patients demonstrated large SP and Ten (41.7%) had a small SP. In some cases of SP areas, hair growth was noticed after the treatment. As an alternative in other cases, the areas of SP didn’t show hair growth compared to the other sites. داء الثعلبة لها أنواع مختلفة، علاوة على ذلك يمكن التنبؤ بخطورتها من خلال التأثير علي مناطق اخرى غير بصيلة الشعر مثل الأظافر والعينين ورقعة السلمون على العنق. كما ذكر مؤلفون سابقون، كان الهدف من هذه الدراسة هو تحديد ما إذا كان وجود رقعة السلمون على منتصف العنق وما إذا كان حجمها مرتبطًا بتكرار داء الثعلبة بعد توقف العلاج والانذار بتشخيص اكثر خطورة. قمنا ببحث عن سلسلة حالات مكونة من 24 مريضًا يعانون من داء الثعلبة المتكرر في وجود رقعة السلمون منذ الولادة في الفترة من مارس 2022 إلى أبريل 2023 في مستشفى طرابلس المركزي وفي عيادة خاصة. لقد وجدنا أن غالبية الحالات تم تشخيصها على أنها مصابة بداء الثعلبة من نوعophiasis(العدد = 11، 45.8٪) منهم عشرة (91٪) كانوا من الإناث ويمكن تفسير ذلك على أنه مؤشر على الخطورة حيث أن نوعophiasisيصاحب حالات الاكثر خطورة في داء الثعلبة . الحالات الأخرى كانت من نوع Universalis (العدد = 9، 37.5%) ونوع )Totalisالعدد = 2، 8.3%)، ونوع المتعدد (العدد = 1، 4.2%). وأظهر 11 (45.8٪) من المرضى أن لديهم بقعة سلمون من الحجم الكبير وعشرة (41.7٪) لديهم الحجم الصغير. في بعض الحالات منطقة بقعة السلمون، لوحظ نمو الشعر بعد العلاج. وعلى العكس فالحالات الاخرى، لم تظهر هذه المناطق نمو الشعر مقارنة بالمواقع الأخرى.